As reservas de surfe e a conservação da biodiversidade - Albuquerque, Bruna Bruzaca Gomes de (2022)
The ocean performs essential functions for life on Earth and has had its use and exploitation intensified over time so that efforts to conserve it are urgent. Surfing is one of the fastest growing sports in the world and, due to its direct connection with nature and the ocean, it plays an essential role in raising awareness of the need for conservation. Around the world, several innovative models of nature conservation have emerged and it is also up to the Law to investigate and frame them, whenever possible. The present work aims, through the methodology of literature review and case studies, to understand if the existing tools for the protection of surf breaks can be recognized as in situ conservation tools and, consequently, count towards the achievement of the related international goals. It was concluded that, among the two existing conservation tools, Protected Areas and Other Effective Area-Based Conservation Measures (OECMs), the second is presented as the most adequate model for the protection of surf breaks.